PROCUREMENT PROCESS APPROVALS AND THEIR CONTRIBUTION TO HIGH QUALITY MARKET DRIVEN PRODUCTS: A CASE OF THE UNITED NATIONS ORGANIZATION STABILIZATION MISSION IN THE DEMOCRATIC REPUBLIC OF CONGO (MONUSCO) ENTEBBE SUPPORT BASE - Marius, Gatta Ouyabaka (International Journal of Supply Chain Management, 2017)
Purpose: The purpose of this study was to identify how process approvals contribute to high quality market driven products. Methodology: The study employed a descriptive case study design. The target population comprised of 261 employees of MONUSCO Entebbe Support Base holding international, United Nations Volunteers (UNV) and National contracts. Random and purposive sampling techniques were specifically used to select samples for this study. Data was collected using questionnaires and interview guides. The quantitative data was further analysed using SPSS for descriptive and inferential statistics while the qualitative data was analysed using content analysis. Findings: The study findings showed that sourcing activity has been used to identify and select the most qualified bidder with quality products and services needed in MONUSCO ESB since it facilitates adequate gathering and collection of all relevant information on the bidder. The findings further showed that market capability analysis is effectively carried out to determine where to procure the type and quality of products, materials, goods and services needed at the base. It was also found that delivery schedules that fit in MONUSCO requirements are drawn with the suppliers and this has improved on the delivery schedules met by the individual suppliers for all kinds of materials, goods and services required by the MONUSCO users' departments. Staff were found to be aware of vendors' evaluation process in their respective sections which improved on the supplier sourcing and selection process for a fair and unbiased evaluation of the bidders in the base. It was further found that the quality of materials depended on their technical specifications as approved at MONUSCO and not on their price which led to client satisfaction amongst the user departments in the base. In addition, evaluation of vendors starts during the delivery of goods/services and works in the base and this has strengthened the achievement of value for money through specifications, quantity and quality standards agreed on at the time of contract award at the base. Unique contribution to theory, practice and policy: The study recommends that MONUSCO procurement section to adequately select the right suppliers to provide the required goods and services. The organization should establish agreements with suppliers with clear guidelines on operations during service delivery. The study further recommends that members of the MONUSCO contracts committee should be recruited and allocated duties basing on the competencies as well as experience in procurement activities within the UN environment.